Кормовые растения червецов и щитовок (Homotera, Coccoidea) Крыма - Терезникова, Е.М. (Вестник зоологии, 1968)
The material of this article is based on the author's own collections in the territory of the Crimean region and the data of the literature. Food plants of Coccoidea are extremely various. 147 species of food plants from 48 families are registered for Coccoidca in the Crimea.